Kinematic analysis of "Lou Yun" vaults performed by top level male gymnasts: Relationship between kinematic variables and judges' score - Farana, R.; Uchytil, J.; Zahradnik, D.; Jandacka, D. (Acta Universitatis Palackianae Olomucensis. Gymnica, 2013)
In gymnastics judging, evaluation of routines in their execution is based on form and technique displayed during the performance. A vaulting performance takes a short time and is affected by the quantity of biomechanical variables. The significant relationships between the vault score and specific aspects of the gymnast`s vault should motivate coaches to monitor these variables as a part of training or routine testing. OBJECTIVE: The purpose of the study was to determine the biomechanical variables that are related to a successful performance of Lou Yun vaults performed by top level male gymnasts during the World Cup competition. METHODS: Ten top-level male gymnasts participated in this study. For the 3D kinematic analysis, two digital camcorders with a frame rate of 50 Hz were used. The data was digitized by Simi Motion software. The Hay and Reid method (1988) was used to identify the biomechanical variables that determine the linear motions of the Lou Yun vaults. A correlation analysis was used to establish the relationship between the biomechanical variables and the judges` scores. The level of statistical significance was determined at the value of p RESULTS: Six out of 24 examined variables showed significant correlations with the scores. A significant correlation was found in the maximum height of the body centre of mass in the second flight phase (r = .68), in the height of centre of mass at mat touchdown (r = .75), in the relative height from table take-off to mat touchdown (r = -.85), in the duration of the table contact phase (r = -.71), in the duration of the second flight phase (r = .62) and in the vertical velocity of body centre of mass at table take-off (r = .70). CONCLUSIONS: The results of the study suggest that a successful execution of Lou Yun vaults and the achievement of a higher score required: to minimize duration of table support phase; to maximize the vertical velocity in the table take-off phase; to maximize the amplitude of the second flight phase, which is determined by the duration of the second flight phase, by the maximum height of the body centre of mass in the second flight phase, and by the distance from the vaulting table during landing; and to maximize the height of the body centre of mass in the mat contact phase.